Sociodemographic factors related to internet addiction among adolescents in Serbia - Pjevač, Ana; Safiye, Teodora; Jovanović, Mirjana (Vojnosanitetski pregled, 2024)
Background/Aim. The term “internet addiction” (IA) describes a compulsive behavior associated with any online activity that disrupts everyday social interactions. The aim of this study was to determine risk factors and predictors of the development of IA in adolescents. Methods. Data were collected using an online form consisting of demographic data, questions related to the use of the Internet, and the Internet Addiction Test (version for adolescents). Results. A total of 1,669 respondents participated in this research; 1,040 of them (62.3%) were female, 590 (35.4%) were male, and 39 (2.3%) did not want to declare their gender. The average age of the respondents was 15.09 ± 1.757 years. Significant factors in the multivariate factor analysis model were age, addictive substance use frequency, purpose, and time spent on the Internet (p < 0.05). Analysis results indicate that the risk of developing IA was higher if an adolescent spent 1–3 hrs and more than 3 hrs daily on the Internet (2.8 and 8.2 times, respectively). With increasing age numbers for one unit (year), the risk of developing IA was decreasing by 11.3%. Conclusion. According to the findings of the present study, the relationship between IA and age, addictive substance use frequency, purpose, and time spent on the Internet has been proven. These results should be highlighted so that educators and all those who work with children could create targeted treatments to prevent the development of IA in adolescents.
Keywords: adolescent; internet use; surveys and questionnaires; technology addiction